'Patenting' Karagoz: UNESCO, nationalism and multinational intangible heritage - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
Borne by people, intangible heritage is not tied to a territory, nor it is necessarily found within the borders of a single country. The 2003 UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage recognises this transnational character of intangible heritage and encourages States Parties to submit joint, multinational, nominations to its lists when a cultural element is commonly found in their territory. Despite such encouragement, there have been very few multinational inscriptions on the Convention's lists so far. This article examines nationalistic approaches to intangible heritage as a major obstacle in this situation. While the Convention calls for international cooperation to safeguard the world's intangible heritage, it inadvertently fosters nationalist claims on cultural traditions on the ground. States Parties may treat the Convention as a patent approval system' and use its lists to register shared traditions as their own national heritage. Their listing on behalf of a single State Party generates conflicts among countries over their origin and ownership. This article examines Karagoz shadow theatre as a case in point.
Keywords: UNESCO; nationalism; multinational intangible heritage; Greece; Turkey; CULTURAL-HERITAGE; POLITICS